Adolescence: The importance of the peer group and friendship - Day, Michael Lewis (1987)
This thesis was submitted for the degree of Doctor of Philosophy and awarded by Brunel University.This thesis is concerned with the nature of the peer group experience and friendship patterns amongst a sample of 3rd, 4th and 5th year secondary school pupils. The thesis has four parts and a General Introduction in which the need for more sociological research in the area of the peer group and friendship is asserted. Certain themes are developed in relation to the peer group and friendship, and arguments for the research established. In the final part of the General Introduction consideration is given to the nature of the sociology of youth in relation to social class and age grading in society. Part One has three Chapters. The first deals with recent research into the peer group, most of which is American in origin with the exception of certain ethnographic studies which have been published in this country over the last few years. In Chapter Two research into friendship is considered with Chapter Three providing a critical evaluation of the research presented. A general schema is provided, drawing on the literature review which provides the basis for the development of research methods and the subsequent research programme. Part Two establishes the basis for the thesis research and has one chapter. Four objectives are explored. The first concerns the importance of friendship to young people, the second with levels of friendship, the third with deriving definitions of friendship. The final objective examines the effects of age and sex on friendship and is compared with the findings from four significant studies undertaken in this area. Sociometry is considered in relation to "mapping" a group, a self esteem inventory is developed and the Higher Schools Personality Questionnaire evaluated with a view to measuring a number of personality traits. In Chapter Five of Part Three a research design for quantitative and qualitative research is presented. The data are presented in Chapters Six and Seven. 371 young people completed a questionnaire into their friendship and peer relations and two peer groups were intensively involved in group discussion in an endeavour to provide more detailed information on friendship and peer activities. The final part, Chapter Eight, is devoted to a detailed consideration of the findings from the research in the light of the established objectives. An appraisal is undertaken of the extent to which new knowledge has been provided in the social sciences regarding the peer group and friendship